Perencanaan Srategis Sistem Informasi Pariwisata menggunakan Framework Cobit 5: Studi Kasus : Dinas Kebudayaan dan Pariwisata Provinsi Jambi - Dewi Novitasari; Dr. Tata Sutabri (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
Failure to plan the utilization of Information Systems and Information Technology results in organizations/institutions facing a relatively high increase in financial expenses. Advances in information technology make Information Systems and Information Technology have an important role for the running of an organization today. Information system strategic planning is needed that is aligned with organizational goals that are in accordance with organizational needs and can provide benefits. Strategic planning must be in accordance with the needs of activities and organizational goals. This research was conducted using the Cobit 5 Framework with the Ward and Peppard method by applying several stages of analysis. It is known that the priority of the BSC Cobit 5 Dimension sequentially is financial, learning and growth, internal and costumer. While TI's goal of the cobit 5 process, number 7 gets the first priority where the processes that are the first order are EDM04, APO01 and APO07 and so on.